Defect-band mediated ferromagnetism in Gd-doped ZnO thin films - Venkatesh, S. (2015)
Gd-doped ZnO thin films prepared by pulsed laser deposition with Gd concentrations varying from 0.02–0.45 atomic percent (at. %) showed deposition oxygen pressure controlled ferromagnetism. Thin films prepared with Gd dopant levels (<Gd 0.112 at. %) at low oxygen deposition pressure (<25 mTorr) were ferromagnetic at room temperature. Negative magnetoresistance, electric transport properties showed that the ferromagnetic exchange is mediated by a spin-split defect band formed due to oxygen deficiency related defect complexes. Mott's theory of variable range of hopping conduction confirms the formation of the impurity/defect band near the Fermi level.